Christianization of Fairies in Armenia - Jivanyan, Alvard (Armenian Folia Anglistika, 2007)
The Armenian church was quite intolerant towards any expression of pagan faith in the early periods of Christianity. Pagan gods and spirits (fairies) were either rejected or labeled as “evil” or were simply “Christianized” acquiring the necessary features to be able to survive in the realm of the new religion. This phenomenon can be observed in various folklore narrations, namely in national tales. The article draws parallels between similar phenomena in other cultures.